Evaluation of a novel automated allergy microarray platform compared with three other allergy test methods. (13th January 2016) - Williams, P; Önell, A; Baldracchini, F; Hui, V; Jolles, S; El-Shanawany, T
Summary: Microarray platforms, enabling simultaneous measurement of many allergens with a small serum sample, are potentially powerful tools in allergy diagnostics. We report here the first study comparing a fully automated microarray system, the Microtest allergy system, with a manual microarray platform, Immuno-Solid phase Allergen Chip (ISAC), and two well-established singleplex allergy tests, skin prick test (SPT) and ImmunoCAP, all tested on the same patients. One hundred and three adult allergic patients attending the allergy clinic were included into the study. All patients were tested with four allergy test methods (SPT, ImmunoCAP, Microtest and ISAC 112) and a total of 3485 pairwise test results were analysed and compared. The four methods showed comparable results with a positive/negative agreement of 81–88% for any pair of test methods compared, which is in line with data in the literature. The most prevalent allergens (cat, dog, mite, timothy, birch and peanut) and their individual allergen components revealed an agreement between methods with correlation coefficients between 0·73 and 0·95. All four methods revealed deviating individual patient results for a minority of patients. These results indicate that microarray platforms are efficient and useful tools to characterize the specific immunoglobulin (Ig)E profile of allergic patients using a small volume of serum sample. The results produced by the Microtest system were in agreement with diagnostic tests in current use. Further data collection and evaluation are needed for other populations, geographical regions and allergens.